2018
DOI: 10.1021/acs.analchem.7b04788
|View full text |Cite
|
Sign up to set email alerts
|

Combinatorial in Vitro and in Silico Approach To Describe Shear-Force Dependent Uptake of Nanoparticles in Microfluidic Vascular Models

Abstract: In the present work, we combine experimental and computational methods to define the critical shear stress as an alternative parameter for nanotoxicological and nanomedical evaluations using an in vitro microfluidic vascular model. We demonstrate that our complementary in vitro and in silico approach is well suited to assess the fluid flow velocity above which clathrin-mediated (active) nanoparticle uptake per cell decreases drastically although higher numbers of nanoparticles per cell are introduced. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 38 publications
0
18
0
Order By: Relevance
“…NPs uptake was dose-dependent parallel to the increase of the flow stimulation up to a critical value (2.25 µL min −1 or 4 dyn cm −2 ). At a higher mechanical load, NPs absorption decreased with inverse relation between concentration and force [190].…”
Section: Absorptionmentioning
confidence: 96%
“…NPs uptake was dose-dependent parallel to the increase of the flow stimulation up to a critical value (2.25 µL min −1 or 4 dyn cm −2 ). At a higher mechanical load, NPs absorption decreased with inverse relation between concentration and force [190].…”
Section: Absorptionmentioning
confidence: 96%
“…For example, it has been shown that shear stress influences nanoparticle uptake of endothelial cells where higher flow rates led to reduced uptake. Using an in vitro as well as in silico approach, Charwat et al (2018) found that clathrin-mediated uptake of nanoparticles is drastically reduced when exceeding shear forces of 1.8 dyn/cm 2 , implying an important role of shear stress when investigating in vitro nanoparticle uptake. Another study, published by Griep et al (2013) , successfully recreated the smallest unit of the blood brain barrier using immortalized brain endothelial cells to study barrier integrity in the presence of physiological shear force.…”
Section: Microfluidic Mechanobiology In Monolayers and Barrier Modelsmentioning
confidence: 99%
“…Among these, self-assembled and autologously formed vascular networks in hydrogel-laden microfluidic channels have proven ideal for studying fundamental biological processes, diseases, and exposure to drugs or toxic compounds. 16,23,24 The success of vasculature-onchip systems is inherently linked to the unique capability to adjust physiological flow conditions, 15 shear forces, 25 nutrient gradients, 14 and biomechanical cues. 11,26 Additionally, the characteristic design flexibility of microfluidic technology has led to the generation of a variety of customized cultivation chamber geometries capable of precisely controlling cellcell, cell-matrix, and cell-molecule interactions.…”
Section: Introductionmentioning
confidence: 99%
“…28 As an example, mechanobiological stimulation via directional interstitial fluid flow increases tumor cell entry into lymphatic capillaries and stimulates lymphatic sprouting. 29,18 Emulating the mechanobiological environment regarding matrix elasticity, 30 fluid flow, 31 or nutrient gradients [32][33][34] is crucial for developing reliable and accurate in vitro systems. We have previously shown that mechanobiological control over shear stress and growth factor gradients allows manipulation of vascular network formation and nanoparticle uptake by endothelial cells.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation